Determining the Complex Permittivity of Building Dielectric Materials using a Propagation Constant Measurement - Mohammed Bendaoued; Jaouad Terhzaz; Rachid Mandry (International Journal of Electrical and Computer Engineering (IJECE), 2017)
This paper presents a technique to determine the Dielectric constant and dielectric loss of the building dielectric materials using propagation constant measurements. The material sample is loaded in an X-band (8.5GHz-12.5GHz) rectangular waveguide and its two port S-parameters are measured as a function of frequency using a Vector Network Analyzer without TRL Calibration. The results obtained from samples of dielectric materials  (Air, Cellular concrete and  Wood)  on  the  X-band  frequencies show  the  validity  of  the  proposed technique to determine the complex permittivity of the building dielectric materials on the X-band frequencies.